How to Make the Word-Length Effect Disappear in Letter-by-Letter Dyslexia. - Fiset, Daniel; Arguin, Martin; Bub, Daniel (Psychological Science., 2005)
A study was conducted to examine whether letter confusability, via its apparent influence on parallel processing, is the cause of the protracted word-length effect that is diagnostic of letter-by-letter (LBL) dyslexia. Participants were seven LBL patients. Findings demonstrated that the word-length effect can be abolished if words of various lengths are matched on the sum of the confusability of their letters. The findings demonstrated the significant contribution of parallel processing to explicit word recognition in LBL dyslexia and indicated that an impairment in letter processing is fundamental to causing the disorder.